Dental development of children and adolescents with cleft lip and palate - Francielle Topolski; Rafael Boscheti de Souza; Osmar Aparecido Cuoghi; Luciana Reichert da Silva Assunção (Universidade Estadual de Campinas, 2010)
Aim: To evaluate the dental development of Brazilian children and adolescents with cleft lip and palate. Methods: The sample consisted of 107 panoramic radiographs of children and adolescents with cleft lip and/or palate (cleft group) and 107 panoramic radiographs of children and adolescents without cleft lip and/or palate (control group), with chronological ages ranging from 6 to 15 years, matched in gender and chronological age within 60 days. Radiographs were digitized and masked and dental age was assessed using the method described by Demirjian et al. (1973). Three trained examiners conducted the assessments. Each examiner evaluated the radiographs three times. Data were statistically analyzed using non-parametric tests and univariate linear regression (p<0.05). Results: The dental age was overestimated in relation to the chronological age in both groups (p<0.0001). Compared to the control group, there was a delay in the dental age in the cleft group of 0.17 years (2.1 months). However, no statistically significant difference in the dental age between the cleft and the control group was found even when considering the different cleft types (p=0.152). Conclusions: There was no statistically significant difference in the dental age between the cleft and the control groups. The evaluation of dental development in individuals with cleft lip and palate should be approached in the same way as in individuals without clefts, with a focus on the individualization of diagnosis and treatment planning.